2018
DOI: 10.1080/03019233.2018.1464284
|View full text |Cite
|
Sign up to set email alerts
|

Thermal physical properties and dephosphorisation kinetics of rare earth oxides containing slags

Abstract: The melting properties and viscosity of CaO-SiO 2 -MnO-La 2 O 3 -CeO 2 slags, with mass ratios of 0.97 and 1.05 between CaO and SiO 2 , were measured using the hot stage microscopy method and rotating cylinder method, respectively. In addition, the dephosphorisation kinetics of rare earth (RE) oxides containing slags was studied. For increasing mass contents of the RE oxides, La 2 O 3 and CeO 2 (0, 3, 6, 9, and 12 wt.%), in the slag, the melting temperature initially decreases and then increases. Minimum value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…However, dephosphorization process is a liquid phase reaction, controlled by material diffusion in the liquid phase and interface chemical reaction. A lower temperature leads to an uneven melting of the slag, and the transfer of material is rate-limiting, which leads to a poor kinetics of dephosphorization [16]. Therefore, when the temperature is below 1,550°C, the dephosphorization efficiency is mainly influenced by the kinetics, and an increase in temperature up to 1,550°C causes an increase in dephosphorization efficiency.…”
Section: Dephosphorization Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…However, dephosphorization process is a liquid phase reaction, controlled by material diffusion in the liquid phase and interface chemical reaction. A lower temperature leads to an uneven melting of the slag, and the transfer of material is rate-limiting, which leads to a poor kinetics of dephosphorization [16]. Therefore, when the temperature is below 1,550°C, the dephosphorization efficiency is mainly influenced by the kinetics, and an increase in temperature up to 1,550°C causes an increase in dephosphorization efficiency.…”
Section: Dephosphorization Temperaturementioning
confidence: 99%
“…Based on these conditions, Xi et al [14] distribution between CaO-SiO 2 -MnO-Ce 2 O 3 -La 2 O 3 slags and ferromanganese alloy, and the results showed that an increase in the RE oxide content in molten slags improves the phosphorus distribution ratio. However, RE oxides have a limited solubility in molten slags [15], while excessive RE oxides in the slags cause an increase in the molten temperature and viscosity, thus deteriorating the dephosphorization kinetics [16].…”
Section: Introductionmentioning
confidence: 99%